The defiant: protest movements in post-liberal America - Barrett, Dawson (New York University Press, 2018)
Introduction: the American protest tradition -- The forests for the trees: neoliberalism and the environment -- Rebel spaces: youth, art, and countercultures -- Links in the chain: workers' rights networks and globalization -- Invasion and occupation: fighting the "war on terror" -- Eviction and occupation: austerity and the global recession -- Epilogue: Kennedy International Airport, 2017